2001
DOI: 10.1021/bi011378s
|View full text |Cite
|
Sign up to set email alerts
|

Role of the Chain Termini for the Folding Transition State of the Cold Shock Protein

Abstract: Residues Arg3 and Leu66 are crucially important for the enhanced stability of the cold shock protein Bc-Csp from the thermophile Bacillus caldolyticus relative to its homologue Bs-CspB from the mesophile Bacillus subtilis. Arg3, which replaces Glu3 of Bs-CspB, accounts for two-thirds of the stability difference and for the entire difference in Coulombic interactions between the two proteins. Leu66, which replaces Glu66 of Bs-CspB, contributes additional hydrophobic interactions. To elucidate the role of these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
46
1

Year Published

2003
2003
2012
2012

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(62 citation statements)
references
References 38 publications
15
46
1
Order By: Relevance
“…We thus have no evidence for native state topology in collapsed unfolded CspTm, in contrast to NMR experiments on staphylococcal nuclease (8) and eglin (52) at high concentrations of urea and in contrast to suggestions from simulations (53). Similarly, there is no obvious relation to the transition state structure (54). Our observation is in contrast to recent measurements on chymotrypsin inhibitor 2 and acyl-CoA-binding protein, where indications were found for a substantial deviation of the collapsed denatured state from Gaussian chain behavior (17) possibly involving folding intermediates (55).…”
Section: Discussioncontrasting
confidence: 87%
“…We thus have no evidence for native state topology in collapsed unfolded CspTm, in contrast to NMR experiments on staphylococcal nuclease (8) and eglin (52) at high concentrations of urea and in contrast to suggestions from simulations (53). Similarly, there is no obvious relation to the transition state structure (54). Our observation is in contrast to recent measurements on chymotrypsin inhibitor 2 and acyl-CoA-binding protein, where indications were found for a substantial deviation of the collapsed denatured state from Gaussian chain behavior (17) possibly involving folding intermediates (55).…”
Section: Discussioncontrasting
confidence: 87%
“…Studies of folding transition states by -analysis point to key interacting residues that have high -values (Ն0.35) in the N-and C-terminal secondary structural elements of a number of proteins. Examples include the terminal ␣-helices of acyl-coA binding protein (36), spectrin R16 (37), and the bacterial immunity proteins Im7 and Im9 (38,39); the terminal ␤-strands of muscle acylphosphatase (40), human procarboxypeptidase A2 (40,41), and PsaE (42); the terminal ␤-hairpins of protein G (43), FNIII domain 10 (44), and CspB (45,46); and the N-terminal ␣-helix and C-terminal ␤-hairpin of CI2 (47). The recently developed -analysis of folding transition states identified contacting residue pairs in the N-and C-terminal ␤-strands of ubiquitin (48,49).…”
Section: Resultsmentioning
confidence: 99%
“…This argument is also supported by the studies of Reid et al 12 that the presence of an oligonucleotide can increase the folding rate as such an oligonucleotide can bind the hydrophobic residues located in b2 and b3. Perl et al 9 have proposed that the N-terminal region is folded but the C-terminal is not in the TS. Furthermore, Garcia-Mira et al 7 suggested that the development of native contacts between b1 and b4 is crucial for reaching the TS.…”
Section: The Folding Mechanism Of Cspmentioning
confidence: 99%
“…The dependence of rate constants of refolding and unfolding on denaturant concentration suggests that the transition state (TS) of Csp should be very compact. [3][4][5][6][7][9][10][11][12][13]15 On the other hand, f-value analysis, proposed by Fersht et.al., 23 has served as a powerful method to study the TSE. So far, f-value analysis has been used to systematically study the TSE of Csp from B. subtilis.…”
Section: Introductionmentioning
confidence: 99%